2017
DOI: 10.1017/s0954579417000360
|View full text |Cite
|
Sign up to set email alerts
|

Maternal mind–mindedness and toddler behavior problems: The moderating role of maternal trauma and posttraumatic stress

Abstract: Maternal mind-mindedness (MM) reflects a caregiver's tendency to view a child as an individual with an independent mind. Research has linked higher MM with more favorable parenting and child adaptation. The aim of this study was to examine whether MM was associated with toddlers' behavior problems and competence, and the moderating role of trauma and posttraumatic stress disorder (PTSD) in a sample (N = 212) of adolescent mothers and their toddlers. MM was coded from maternal utterances during free play; mothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 58 publications
5
15
1
Order By: Relevance
“…We had speculated that non‐attuned comments might be more common in a stressful interaction context, when the attachment systems of both mother and infant were likely activated. Although the proportion of non‐attuned comments was very low (1%) and directly comparable with prior research where figures are reported (e.g., Meins et al., , ), in the current study, 25% of mothers made at least one such comment, while several studies have reported that fewer than 10% of mothers do so (Bernier et al., ; Easterbrooks et al., ). Interestingly, only one mother (from a sample of 31) in the study by Bigelow et al.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We had speculated that non‐attuned comments might be more common in a stressful interaction context, when the attachment systems of both mother and infant were likely activated. Although the proportion of non‐attuned comments was very low (1%) and directly comparable with prior research where figures are reported (e.g., Meins et al., , ), in the current study, 25% of mothers made at least one such comment, while several studies have reported that fewer than 10% of mothers do so (Bernier et al., ; Easterbrooks et al., ). Interestingly, only one mother (from a sample of 31) in the study by Bigelow et al.…”
Section: Discussionsupporting
confidence: 89%
“…Few studies have examined associations between sensitivity and non-attuned comments, with evidence limited to this single sample. Most studies do not report on nonattuned comments at all, as they are very infrequent and most mothers do not make any (Bernier, McMahon, & Perrier, 2017;Easterbrooks, Crossman, Caruso, Raskin, & Miranda-Julian, 2017;Licata et al, 2014;McMahon, Camberis, Berry, & Gibson, 2016). Meins et al (2012) in the study cited above reported an average proportional score for non-attuned comments of just 1.58% which is consistent with other research in community samples.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…For example, maternal mind-mindedness has been demonstrated to predict lower internalising and externalising problems only amongst pre-schoolers from low socio-economic status families . Conversely, Easterbrooks et al (2017) found that mind-mindedness was associated with fewer behavioural problems only in infants of trauma-exposed adolescent mothers who did not meet criteria for posttraumatic stress disorder. Considering that maternal mind-mindedness is potentially modifiable (Schacht et al, 2017), further research is necessary to clarify the contexts under which this interactive quality may offer developmental benefits.…”
Section: Prenatal Maternal Stress: Postnatal Mediators and Moderators?mentioning
confidence: 88%
“…Research supports the facilitative influence of "appropriate" maternal mind-mindedness on a range of child developmental domains, including attachment security , executive function and self-regulation Bernier et al, 2017) and social cognition (Laranjo, Bernier, Meins, & Carlson, 2014;. The few studies that have investigated the relationship between maternal mind-mindedness and child behaviour problems (Easterbrooks et al, 2017;Hughes, Aldercotte, & Foley, 2016) suggest that these associations are complex and may be influenced by contextual factors . For example, maternal mind-mindedness has been demonstrated to predict lower internalising and externalising problems only amongst pre-schoolers from low socio-economic status families .…”
Section: Prenatal Maternal Stress: Postnatal Mediators and Moderators?mentioning
confidence: 98%